2012
DOI: 10.1002/mnfr.201200122
|View full text |Cite
|
Sign up to set email alerts
|

Marie Ménard apples with high polyphenol content and a low‐fat diet reduce 1,2‐dimethylhydrazine‐induced colon carcinogenesis in rats: Effects on inflammation and apoptosis

Abstract: Inflammation may increase cancer risk, therefore, we studied whether polyphenol-rich Marie Ménard (MM) apples with reported anti-inflammatory activity prevent 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis in rats and, likewise whether high-fat (HF) diet promoting carcinogenesis, may affect inflammation. DMH-induced rats were fed for 15 weeks with: an HF diet (23% corn oil w/w); an HF diet containing 7.6% w/w lyophilized MM (apple diet (AD)); a low-fat (LF) diet and an HF diet containing piroxicam (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The prebiotic effects of apples have been of particular interest in the research community due to their frequent consumption in society. The modification of microbiota composition through apple components along with the direct effect of polyphenols may have cardioprotective effects, such as reducing inflammation [ 76 ] and total cholesterol levels [ 74 , 77 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…The prebiotic effects of apples have been of particular interest in the research community due to their frequent consumption in society. The modification of microbiota composition through apple components along with the direct effect of polyphenols may have cardioprotective effects, such as reducing inflammation [ 76 ] and total cholesterol levels [ 74 , 77 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…Inhibition of the NF-kB transcription factor, suggested as a potential mechanism [ 19 ] [ 207 ] has also been reported in other human cell studies with apple extracts [ 209 , 210 ]. The beneficial effect of Marie Menard apples was further confirmed in rats showing decreased colonic and systemic inflammation [ 22 ]. Furthermore apple pectin has been associated with anti-inflammatory effects in animal studies by down regulating pro-inflammatory cytokine expression and immunoglobulin production in the colon [ 211 ] and systematically by reducing plasma TNF-α [ 21 ].…”
Section: Cardiovascular Disease Riskmentioning
confidence: 99%
“…Epidemiological studies support the view that frequent apple consumption is associated with a reduced risk of chronic pathologies such as cardiovascular disease, specific cancers, and diabetes [ 6 , 7 , 8 , 9 , 10 ]. Data from intervention studies in humans and animals suggest that apple intake may positively affect lipid metabolism [ 11 , 12 , 13 , 14 , 15 ], weight management [ 16 ], vascular function [ 17 , 18 ] and inflammation [ 19 , 20 , 21 , 22 ]. Apples are a rich source of polyphenols and fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TFAs are known for their ability to increase expression of inflammatory markers such as IL-6 and TNF-α [4, 52] and there is evidence that exposure to a high-fat diet increases inflammation in the colon [14, 15, 53] while high-polyphenol diet reduces this process [54]. Previous studies have shown that in adult offspring of mothers fed TFAs during pregnancy and lactation, high levels of LPS activate TLR-4 and mediate low-grade inflammation [7].…”
Section: Discussionmentioning
confidence: 99%